2017
DOI: 10.2298/abs160614106l
|View full text |Cite
|
Sign up to set email alerts
|

Glycoxidated ferritin induces the release of microparticles positive for Toll-like receptors derived from peripheral blood CD14+ cells

Abstract: Both increased serum ferritin levels and Toll-like receptor (TLR) activation show independent association with the inflammatory processes. During inflammation, cell activation and apoptosis are accompanied by the release of membranederived microparticles (MPs), which are considered to be mediators of intercellular communication as they induce specific responses in target cells. The aim of this study was to determine whether glycated and glycoxidated ferritin induce in vitro release TLR microparticles from CD14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Our recent studies have shown that glycated ferritin serves as a ligand for TLR and that it promotes its in vitro expression in PBMC-derived CD14+ cells from normoglycemic subjects [19][20]. Results from the present study support the finding that glycated ferritin promotes the increased expression of TLR2 and TLR4 in CD14+ PBMC cells from subjects with prediabetes to a significantly greater extent than in cells from normoglycemic subjects.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our recent studies have shown that glycated ferritin serves as a ligand for TLR and that it promotes its in vitro expression in PBMC-derived CD14+ cells from normoglycemic subjects [19][20]. Results from the present study support the finding that glycated ferritin promotes the increased expression of TLR2 and TLR4 in CD14+ PBMC cells from subjects with prediabetes to a significantly greater extent than in cells from normoglycemic subjects.…”
Section: Discussionsupporting
confidence: 86%
“…Activation of NF-κB is the canonical downstream event of the TLR-ligand interaction [8]. In a previous report, we showed that glycated ferritin induces the expression of TLR2, TLR4 and cytokines in PBMC CD14+ cells through differentiation of the myeloid primary response 88 (MyD88)/NF-κB pathway [20]. Although we did not study the independent signaling of MyD88, studies with glycated proteins have shown that NF-κB is activated through the MyD88-dependent pathway [18,37,38].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The flow cytometry analysis (FACS) of the vesicles was executed using calibrated fluorescent latex beads of 1.0 and 0.1 μm diameter to select the capture area of the EVs. 14 20,000 Annexin V+ events were evaluated in the 0.1 -1.0 μm area per assay using a FACSCalibur™ cytometer from Becton Dickinson (San Diego, CA) and the Summit Software Informer ® program (Figure 1).…”
Section: Flow Cytometry Analysis Of Plasma-derived Evsmentioning
confidence: 99%